Capital Structure and Signaling Game Equilibria - Noe, Thomas H. (Review of Financial Studies, 1988)
In this article we model the financing decisions of a firm as a sequential signaling game. We prove that, when insiders have perfect information regarding the firm's future cash flows, the application of “refinements” to the set of admissible equilibria leads to the dominance of debt over equity financing. However, we show that when insiders observe the firm's cash flows imperfectly, there may exist sequential equilibria in which this “pecking order” breaks down and some firms strictly prefer equity to debt financing. We also prove that, despite the breakdown of the pecking order, the announcement effect of equity financing will be negative relative to debt financing.